2003
DOI: 10.1046/j.0818-9641.2002.01145.x
|View full text |Cite
|
Sign up to set email alerts
|

The potential of antibody‐based immunosuppressive agents for corneal transplantation

Abstract: Summary Corneal transplantation is a sight-restorative procedure but its success is limited by irreversible graft rejection, which accounts for up to 50 per cent of failures. The normal eye is an immune-privileged site. Multiple mechanisms maintain ocular privilege, including the blood-eye barrier, the lack of blood vessels and lymphatics in the normal cornea, the relative paucity of mature antigen-presenting cells in the central cornea, the presence of immunomodulatory factors in ocular fluids, and the consti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 150 publications
0
8
0
Order By: Relevance
“…CD4 + T cells are important in controlling the different mechanisms involved in corneal graft rejection and are thus a target for evaluating therapeutic interventions designed to prevent corneal allograft rejection (29). In the present study, it was observed that treatment with anti-CD154 mAb significantly reduced the frequency of total CD4 + T cells that infiltrated the ipsilateral draining lymph nodes, spleens and corneal grafts.…”
Section: Discussionmentioning
confidence: 99%
“…CD4 + T cells are important in controlling the different mechanisms involved in corneal graft rejection and are thus a target for evaluating therapeutic interventions designed to prevent corneal allograft rejection (29). In the present study, it was observed that treatment with anti-CD154 mAb significantly reduced the frequency of total CD4 + T cells that infiltrated the ipsilateral draining lymph nodes, spleens and corneal grafts.…”
Section: Discussionmentioning
confidence: 99%
“…Monoclonal antibodies and other biologics are not used routinely in corneal transplantation, but may be useful for both prophylaxis and for rescue after graft rejection (reviewed in [99,84]). CAMPATH-1H, in particular, has been shown to be effective in rescuing corneal grafts undergoing acute rejection.…”
Section: Immunosuppression For Corneal Transplantationmentioning
confidence: 99%
“…44 Monoclonal antibodies and other biologics are not used routinely in corneal transplantation, but may be useful for both prophylaxis and for rescue after graft rejection. 30,45 CAMPATH-1H, a monoclonal antibody that rapidly induces lymphopenia after IV infusion, has been shown to be effective in rescuing corneal grafts undergoing acute rejection. The toxicity profile of this drug, which is licensed for the treatment of leukemia, is such that it is not recommended in corneal transplantation.…”
Section: Novel Agentsmentioning
confidence: 99%